Influence of feed form and age of broilers on energy utilisation of feed ingredients : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Animal Science (Poultry Nutrition) at Massey University, Palmerston North, Manawatu, New Zealand - Khalil, Mahmoud Mohamed (Massey University, 2022)
The accurate determination of the available energy of feed ingredients is crucial to optimise their inclusion in feed formulations and to improve the profitability and sustainability of poultry production. The metabolisable energy (ME) is commonly used for energy evaluation and formulating the diets for poultry. However, there are some limitations and several factors that influence the precision of the evaluation of the ME content of feed ingredients and diets. The current thesis investigated some of the unexplored research gaps on the ME of the commonly used feed ingredients in broiler diets. The first study presented in Chapter 3 was conducted to investigate the influence of feed form (FF; mash vs. pellet) on the apparent metabolisable energy (AME) and nitrogen-corrected AME (AMEn) of 7 single feed ingredients, four cereal grains (wheat, sorghum, barley, and maize) and three protein sources (soybean meal; SBM, canola meal; CM, and meat and bone meal; MBM). The influence of broiler age AMEn of cereal grains was investigated in Chapter 4 (direct method) and Chapter 5 (substitution method). The fourth experiment reported in Chapter 6 examined the effect of broiler age on the AMEn of protein sources. The experiments discussed in Chapter 7 were unique in that a novel methodology was developed for the quantification of the ileal endogenous energy losses (IEEL) in broiler chickens and for the correction of apparent ileal digestible energy (AIDE) to true (TIDE) ileal digestible energy of cereal grains (wheat, sorghum, barley and maize). The last trial of the thesis reported in Chapter 8 was conducted to refine-tune the IEEL methodology developed in Chapter 7 and to determine the influence of age and dietary cellulose contents on the IEEL estimates in broiler chickens. Data reported in Chapter 3 demonstrated that FF influenced the AMEn of feed ingredients. Pelleting increased the AMEn of all cereal grains by an average of 0.22 MJ/kg. However, for protein source ingredients, FF influence was ingredient-dependent. Pelleting increased the AMEn of CM by 0.57 MJ/kg, had no effect on that of SBM and decreased the AMEn of MBM by 0.56 MJ/kg. The experiment reported in Chapter 4 investigated the influence of broiler age on the AMEn of cereal grains using the direct method. The assay diets were formulated with an inclusion of 962 g/kg of each grain in the diet and pelleted. The data revealed that the age of broiler chickens has a significant impact on the AMEn of cereal grains. The first week of age recorded the highest AMEn for all cereal grains. Thereafter, the AMEn decreased either linearly (sorghum) or quadratically (wheat, barley and maize) with the advancing age of broilers. In the study reported in Chapter 5, the effect of broiler age on the AMEn of cereal grains, from the same batches used in Chapter 4, was examined using the substitution method. A maize-SBM basal diet was formulated and test diets were developed by replacing (w/w) 300 g/kg of the basal diet with each cereal grain. The results showed that the effect of broiler age on the AMEn varied depending on the grain type. Whilst the AMEn of barley and maize were unaffected by age, the AMEn of wheat and sorghum increased with the advancing age of broiler chickens. The determined AMEn values differed between direct and substitution methods, with the substitution method generating lower AMEn values. Data reported in Chapter 6 demonstrated that the AMEn content of SBM and CM was influenced by age of broilers. The first week showed the highest AMEn value for both SBM and CM, followed by reductions for both ingredients up to week 3 and increases thereafter. The studies reported in Chapter 7 present a novel approach to quantify the IEEL in broilers and correct the AIDE of cereal grains (wheat, sorghum, barley and maize) to TIDE enabling comparisons with AMEn. The IEEL was estimated to be 1.45 MJ/kg dry matter intake (DMI) in 21-d old broilers, following the feeding of a glucose-based purified diet and used to calculate the TIDE. The apparent ileal digestibility of dry matter, nitrogen and starch were positively and highly correlated with the TIDE than the AIDE or AMEn. The studies reported in Chapter 8 were conducted to refine the proposed methodology for the estimation of IEEL proposed in Chapter 7 and to investigate the influence of age of broilers and the dietary cellulose contents on IEEL estimates. It was found that the age of broilers had no impact on the IEEL estimates. The IEEL was affected by the cellulose content and the IEEL increased from 0.37 MJ/kg DMI for the diet without cellulose to 1.80 MJ/kg DMI for the diet with 75 g/kg inclusion of cellulose. The findings reported in the current thesis demonstrate that the application of AMEn values determined based on assays using mash diets might result in over- or under-estimation of the available energy content of ingredients in commercial pelleted broiler diets and highlights the need for the use of pelleted diets in energy evaluation assays. The findings also revealed that the effects of age and methodology are relevant in the determination of AMEn of feed ingredients and question the validity of using single AME or AMEn values for feed ingredients in broiler diet formulations across different ages. Another notable contribution was to develop a novel approach to quantify the IEEL in broiler chickens for the first time. The thesis research also provides preliminary data on the TIDE of common cereal grains and highlights the possibility of applying the TIDE as an alternative to the ME system in poultry feed formulation.
Keywords: Broilers (Chickens); Feed utilization efficiency; Feeding and feeds; Age; 300303 Animal nutrition